Importance of Interest Rate on Annuity Prices: A Case Study - Lazoğlu, Çiğdem; Yeldan, Müge; Karabey, Uğur (Afyon Kocatepe University, 2024)
Determination of the accurate discount factor for long-term annuities is crucial in insurance sector. In actuarial studies, the discount factor is typically assumed to be fixed. However using a fixed interest rate in countries with highly fluctuating interest rates can lead to unreliable calculations. In this paper, a Monte Carlo Simulation is constructed for countries with different economic and demographic structures where the Lee-Carter and Vasicek model is used for mortality and interest rate, respectively. Thanks to this scenario the empirical distribution of annuities with both fixed and variable interest rates are established. Risk measures are employed to analyze the impact of mortality volatility and interest rate volatility on the annuity prices. The findings indicate that annuities valued with high interest rate volatility exhibit greater overall volatility. As a result, as the variability of interest rates increases, the volatility of the annuity prices also rises.

Sigortacılıkta, uzun dönemli anüiteler için doğru iskonto faktörünün belirlenmesi son derece önemlidir. Aktüeryal çalışmalarda iskonto faktörü genellikle sabit olarak ele alınmaktadır; ancak yüksek volatiliteli faiz oranına sahip ülkelerde sabit faiz oranı kullanmak, doğru olmayan hesaplamalara neden olmaktadır. Bu çalışmada farklı ekonomik ve demografik yapılara sahip ülkeler için Monte Carlo Simülasyonu oluşturulmuş, simülasyonda ölümlülük için Lee-Carter modeli, faiz için Vasicek modeli tercih edilerek, sabit ve stokastik faiz ile hayat anüitesi fiyatlarının ampirik olarak dağılımı elde edilmiştir. Risk ölçütleri kullanılarak hem ölümlülükteki hem de faizdeki oynaklığın anüite fiyatları üzerindeki etkisi incelenmiştir. Sonuç olarak faiz oranındaki değişkenlik arttıkça, anüite fiyatlarındaki volatilitenin de yükseldiği belirlenmiştir
Faiz Oranının Anüite Fiyatları Üzerindeki Etkisine İlişkin Bir Çalışma
Keywords: Applied Statistics; Uygulamalı İstatistik; Statistics (Other); İstatistik (Diğer)